Brand hate. Issue 1 (21st March 2016) - Zarantonello, Lia; Romani, Simona; Grappi, Silvia; Bagozzi, Richard P.
Abstract : Purpose: – This study aims to investigate the nature of brand hate, its antecedents and its outcomes. Design/methodology/approach: – The authors conduct two quantitative studies in Europe. In Study 1, a measure of brand hate is developed and its effects are tested on behavioral outcomes. In Study 2, the authors show how brand hate and its behavioral outcomes change depending on the reasons for brand hate. Findings: – The study conceptualizes brand hate as a constellation of negative emotions which is significantly associated with different negative behavioral outcomes, including complaining, negative WOM, protest and patronage reduction/cessation. Reasons for brand hate related to corporate wrongdoings and violation of expectations are associated with "attack-like" and "approach-like" strategies, whereas reasons related to taste systems are associated with "avoidance-like" strategies. Research limitations/implications: – The study views brand hate as an affective phenomenon occurring at a point in time. Researchers could adopt a wider perspective by looking at the phenomenon of hate as a disposition/sentiment, not merely as an emotion. They could also adopt a longitudinal perspective to understand how brand hate develops over time and relate it to brand love. Practical implications: – The authors' conceptualization of brand hate offers insights to companies about how to resist and prevent brand hate for one's own brand. Originality/value: – The study provides a first conceptualization of brand hate and develops a scale for measuring it. The authors relate this conceptualization and measurement of brand hate to important behavioral outcomes and different types of antecedents.